Mapping the landscape of professional learning communities for digitalization and STEM: a scoping review of evidence on composition and efficacy - Hartmann, Stefanie; Bardakcioglu, Robin; Schaal, Steffen (Frontiers in Psychology, 2025)
IntroductionThe integration of advanced digital applications within the educational sector remains a significant challenge. It has been determined that extracurricular educational settings possess a considerable capacity to enhance and differentiate digital instruction. However, educators frequently require assistance to transition from the use of existing digital resources to the creation of their own, personalized, customized learning materials. Professional learning communities (PLCs) have been identified as a promising framework in which teachers can collaborate to develop innovative and practical concepts. While the potential of PLCs is widely recognized, research on this topic is fragmented. A multitude of definitions and operationalizations have been proposed regarding the structure and functioning of PLCs. This complicates a systematic investigation of their effectiveness and makes it difficult to distinguish empirically based findings from purely anecdotal reports. Consequently, a definitive evidence base for the design of effective PLCs remains elusive.MethodsThe present study posits that the afore mentioned gap is addressed by means of a scoping review. Utilizing the PRISMA-ScR framework, a systematic analysis of German and English-language literature is conducted with the objective of mapping and synthesizing research on the composition, collaboration, and effectiveness of PLCs in the STEM field or in relation to digitalization.ResultsThe results of the study provide a structured overview of the key characteristics, structure, and success factors of PLCs. The present article elucidates the findings that emerged from a comparative and harmonising analysis of diverging PLCs.DiscussionThe ensuing discussion pertains to the configuration, efficacious design, and execution of professional learning communities, in conjunction with their operational methodologies and investigative endeavours. This synthesis provides a foundation for the conceptualisation of future cooperative initiatives aimed at the development of STEM- or digital educational resources.